2019
DOI: 10.1002/jbio.201800459
|View full text |Cite
|
Sign up to set email alerts
|

Three‐dimensional cellular imaging in thick biological tissue with confocal detection of one‐photon fluorescence in the near‐infrared II window

Abstract: Fluorescence imaging in the second near‐infrared optical window (NIR‐II, 900‐1700 nm) has become a technique of choice for noninvasive in vivo imaging in recent years. Greater penetration depths with high spatial resolution and low background can be achieved with this NIR‐II window, owing to low autofluorescence within this optical range and reduced scattering of long wavelength photons. Here, we present a novel design of confocal laser scanning microscope tailored for imaging in the NIR‐II window. We showcase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…Advantageous imaging effects have been reported in the NIR-II band, such as widefield microscope [11][12][13][14], light sheet microscope [15][16][17], CLSM [18][19][20][21], two-photon and multiphoton microscope [22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…Advantageous imaging effects have been reported in the NIR-II band, such as widefield microscope [11][12][13][14], light sheet microscope [15][16][17], CLSM [18][19][20][21], two-photon and multiphoton microscope [22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…Advantageous imaging effects have been reported in the NIR-II band, such as widefield microscope [11][12][13][14], light sheet microscope [15][16][17], CLSM [18][19][20][21], two-photon and multiphoton microscope [22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…NIR-II light (wavelength 1000-1700 nm), with its longer wavelength and weaker interaction with biological tissues can be a good solution to this problem. In addition, recent studies have shown that compared with NIR-I light, NIR-II light has lower photon dispersion, less tissue absorption, higher sensitivity, relatively higher maximum permissible skin exposure (MPE), more optimal tissue penetration depth (up to 3.5 mm), and better spatial resolution during laser irradiation [21,22]. Therefore NIR-II-responsive tumor imaging has more important applications in biological and medical fields.…”
Section: Introductionmentioning
confidence: 99%